A arquitetura como tragédia da dominação da natureza: um estudo a partir dos escritos estéticos de T.W. Adorno - Marco Tulio Scarpelli Cabral (2002)
The main thesis of this study is that architecture has a tragic dimension,related to the domination of nature. The investigation begins by an inquiry into the concept of architecture, its past and present meaning, by contrast with the fields of art and empirical reality. Next, the question of the domination of nature is investigated alongside the concepts of first nature, second nature and aesthetic domination of nature. In the last part, the pertinence of the category of the tragic for the study of architecture is discussed. A conclusion is reached that the tragic dimension of architecture is in crisis in advanced industrial society, where the clash with first nature loses importance with the advancement oftechnology and the conversion of society into a second nature.